ECOLOGICAL LIFE ZONES OF BRAZIL - Tres, Andressa; França Tetto, Alexandre; Viana Soares, Ronaldo; Wendling, William Thomaz; Henning Santos, Gisele (Floresta, 2020)
Many classification systems were developed to help in the mission of describing climate, but none of them is able to meet all areas of human activity. A system developed by Holdridge in 1947, called “life zones”, is considered the most ecological climate classification system because of the use of biotemperature. Several countries already have a life zones map and the purpose of this study is to classify each Brazilian municipalities according to this system. Temperature, precipitation, altitude and latitude data, provided by Alvares et al. (2013), were applied according to the methodology described by Holdridge (2000). The ecological life zones map was compared with the vegetation map through correlation matrices, which generated indices ranging from 0 to 100%. The results showed that Brazil has 35 life zones. The most common are tropical moist forest and tropical premontane moist forest, covering almost 50% of the country’s area. After the analysis of correlations, we could see that 21 LZs have more than 80% of their surfaces covered by two or less types of vegetation. The LZs distribution was consistent to the characteristics of each region, in terms of vegetation and climate; therefore, the Holdridge system can be considered a relevant and specific option for decision making related to agricultural and forestry activities.